State's Stepping Out of the Dominant Values in Women Empowerment Policy: The Experience of Andhra Pradesh, India. - Ayinagadda, Satyanarayana; Caragata, Lea (Social Development Issues (Follmer Group), 2015)
This article explores why the state of Andhra Pradesh is disregarding the dominant values of Indian society to formulate women-oriented policies. It concludes that the Andhra Pradesh experience of women-oriented policies provides ample evidence that the social action taken by women themselves is playing a vital role in shaping the state's welfare policy. These empowered women are suggesting an alternative paradigm to the state by means of collective expressions at the micro level, thus making the government realize what is essential for the advancement of women. In fact, the women are leading the state, which in turn is leading its people by way of its progressive public policy.